Designing sustainable business models for Islamic entrepreneurship - Elgharbawy, Amal A.M.; Yuhan, Avicenna; Kotachi, Mariam; Erry Yulian Triblas, Adesta (Springer, 2023)
To address the high failure rate of Muslim enterprises caused by the absence of such models, this chapter discusses the crucial importance of sustainable business models in Islamic entrepreneurship. Islamic entrepreneurship is a specific type of business endeavor that needs a special strategy because it has the dual objectives of profitability and Al-Falah (success in this life and the afterlife). The failure rate of Muslim-owned firms is greater than usual because many of them find it difficult to remain profitable while upholding Islamic ideals. To solve this problem, this chapter examines how Islamic and Halal business owners might create and employ sustainable business strategies. It goes into detail on the fundamentals of Islamic entrepreneurship, the significance of sustainable business models, and the particular difficulties experienced by Muslim-owned enterprises. The chapter emphasizes the necessity for a change to sustainable business models that agree with Islamic values by conducting a thorough analysis of the common causes of these failures. It gives Islamic and Halal company owners a manual for understanding and successfully implementing these models, resulting in enterprises that are lucrative and favorably impacting society in accordance with the principles of Al-Falah. In the chapter on future trends and prospects in Islamic entrepreneurship, it is emphasized how important innovation and technology will be in determining this future. It goes into detail on the fundamentals of Islamic entrepreneurship, the significance of sustainable business models, and the challenges faced by Muslim-owned enterprises. The chapter emphasizes the necessity for a change to sustainable business models that agree with Islamic values by conducting a thorough analysis of the common causes of these failures. It gives Islamic and Halal company owners a manual for understanding and successfully implementing these models, resulting in enterprises that are lucrative and favorably impacting society in accordance with the principles of Al-Falah. In the chapter on future trends and prospects in Islamic entrepreneurship, it is emphasized how important innovation and technology will be in determining this future.